Processing retail beef cuts from boxed beef - M.O. Leafgreen; J.H. McCoy (Kansas Agricultural Experiment Station Research Reports, 1979)
This analysis measured efficiencies of a centralized retail meat fabrication facility receiving all beef as boxed or as carcasses. Moving vacuum-packaged, boxed-beef subprimals through a central meat processing facility was more efficient than a corresponding operation with beef carcasses. Boxed beef saved approximately 6.0 cents per pound on wholesale cuts.
Keywords: Cattlemen& #x27; s Day; 1979; Report of progress (Kansas State University. Agricultural Experiment Station); 350; Beef; Retail cuts; Boxed beef